The relationship between the level of knowledge of diabetic diet and blood glucose stability among patients with type 2 diabetes mellitus - Tuhu Sobiron (CV LINK Education Publication, 2026)
Introduction: Type 2 Diabetes Mellitus is a non-communicable disease with a continuously increasing prevalence in Indonesia. Data from the International Diabetes Federation indicate a high diabetes burden and project a further rise in cases. Diabetes control does not rely solely on pharmacological therapy but also on adherence to a diabetic diet. Patients’ level of knowledge regarding diabetic diet plays an important role in maintaining blood glucose stability. Insufficient knowledge may lead to reduce dietary compliance and increased the risk of complications. Objective: To determine the relationship between the level of knowledge of diabetic diet and blood glucose stability among patients with Type 2 Diabetes Mellitus at RSUD Temanggung. Methods: This study employed a quantitative correlational design with a cross-sectional approach. The research instruments: the Knowledge of Diabetic Diet Questionnaire (KDDQ) and a glucometer. Data were analyzed using the Chi-Square correlation test. Results: The level of knowledge regarding the diabetic diet among patients at RSUD Temanggung was predominantly moderate (54.39%), while blood glucose stability was mostly stable (68.42%). The Chi-Square correlation test showed a p-value of 0.001. Conclusion: A significant relationship exists between diabetic diet knowledge and blood glucose stability among patients with Type 2 Diabetes Mellitus at RSUD Temanggung. The study recommends enhancing collaborative, technology-based dietary education programs and encourages future research to apply more comprehensive designs and glycemic control indicators while considering potential confounding factors.